Analysis, Effectiveness, and Impacts of Official Development Assistance (ODA) in Sub-Saharan Africa and Southeast Asia - Pařez, Ondřej (2023)
The aim of the master’s thesis is to verify the effectiveness of ODA on the economic growth of developing states in sub-Saharan Africa and Southeast Asia according to their economic performance through the annual panel data analysis within the years 2000-2020. Based on the econometric analysis of a robust covariance matrix of parameters for the fixed effect models generated by the within estimator method, I find mostly the positive impact of the effectiveness of ODA on real GDP growth per capita. The next statistically significant variables positively influencing the economic growth in almost all observed groups of countries are population growth, human development index (HDI), population older than 15 years with less than primary education and import from the USA. The negative effect on economic growth has the amount of government debt. Moreover, the interaction of ODA with the level of education indicates that ODA has a higher positive effect in countries with a higher number of people older than 15 years with at least primary education. Furthermore, the interaction of ODA with HDI indicates that ODA has a higher positive effect in less developed countries, based on HDI as an indicator. Also, ODA has a highly positive effect in decreasing the negative effects of increasing HDI in lower middle income countries (LMICs). Nevertheless, the effects of government debt and the interaction of ODA with education level on the economic growth of developing countries are very low. Based on results and comprehensive analysis, I formulate relevant economic and policy recommendations in the area of development aid policy.